2014
DOI: 10.1016/j.egypro.2014.11.260
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Effect of Oxidative Degradation of Aqueous Monoethanolamine on Heat of CO2 Absorption, Vapor Liquid Equilibrium and CO2 Absorption Rate

Abstract: Oxidative degradation produces carboxylic acids which are one of the undesirable degradation products and may have a negative impact on the CO 2 separation energy of post combustion capture system. 30wt% MEA solutions mixed with carboxylic acids were regarded as a simulated solution for degraded MEA and effect of the additives on heat of CO 2 absorption, equilibrium CO 2 loading and CO 2 absorption rate were experimentally evaluated by using a differential reaction calorimetry (DRC) apparatus, a pressurized ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This supports the earlier reports by Nakagaki et al. on the CO 2 absorption rate of an MEA solution containing carboxylic acids where they suggested that the detrimental effect of the presence of HSSs can be partly impeded if the CO 2 absorption rate of an absorbing solution is maintained at a high value within richer CO 2 loadings 100 . In their work, Weiland & Sivasubramanian also highlighted the beneficial presence of HSS to the operation of the stripper section alongside their damaging effects to the absorber operation 101…”
Section: Operational Problems Caused By Hssssupporting
confidence: 92%
“…This supports the earlier reports by Nakagaki et al. on the CO 2 absorption rate of an MEA solution containing carboxylic acids where they suggested that the detrimental effect of the presence of HSSs can be partly impeded if the CO 2 absorption rate of an absorbing solution is maintained at a high value within richer CO 2 loadings 100 . In their work, Weiland & Sivasubramanian also highlighted the beneficial presence of HSS to the operation of the stripper section alongside their damaging effects to the absorber operation 101…”
Section: Operational Problems Caused By Hssssupporting
confidence: 92%
“…The pH of virgin 30 wt% MEA, AMP and PZ is 12.31, 12.53 and 12.74, respectively. CO 2 is an acid gas when it reacts with aqueous solutions, and pH decreases with the increase of CO 2 loading because of the acidic reaction through the zwitterion ion concept (Lv et al 2015;Nakagaki et al 2014). In this zwitterion ion mechanism, the reaction between CO 2 and aqueous solvents forms carbamate as an intermediate compound.…”
Section: Effect Of Carbon Loading On Phmentioning
confidence: 99%